Genomic Investigation of Antimicrobial-Resistant Salmonella enterica Isolates From Dead Chick Embryos in China - Elbediwi, Mohammed; Tang, Yanting; Shi, Dawei; Ramadan, Hazem; Xu, Yaohui; Xu, Sihong; Li, Yan; Yue, Min (Frontiers in microbiology, 2021)
Salmonella spp. is recognized as an important zoonotic pathogen. The emergence of antimicrobial resistance in Salmonella enterica poses a great public health concern worldwide. While the knowledge on the incidence and the characterization of different S. enterica serovars causing chick embryo death remains obscure in China. In this study, we obtained 45 S. enterica isolates from 2,139 dead chick embryo samples collected from 28 breeding chicken hatcheries in Henan province. The antimicrobial susceptibility assay was performed by the broth microdilution method and the results showed that 31/45 (68.8%) isolates were multidrug-resistant (≥3 antimicrobial classes). Besides the highest resistance rate was observed in the aminoglycoside class, all the isolates were susceptible to chloramphenicol, azithromycin, and imipenem. Furthermore, genomic characterization revealed that S . Enteritidis (33.33%; 15/45) was a frequent serovar that harbored a higher number of virulence factors compared to other serovars. Importantly, genes encoding β-lactamases were identified in three serovars (Thompson, Enteritidis, and Kottbus), whereas plasmid-mediated quinolone resistance genes ( qnrB4 ) were detected in certain isolates of S . Thompson and the two S . Kottbus isolates. All the examined isolates harbored the typical virulence factors from Salmonella pathogenicity islands 1 and 2 (SPI-1 and SPI-2). Additionally, a correlation analysis between the antimicrobial resistance genes, phenotype, and plasmids was conducted among Salmonella isolates. It showed strong positive correlations ( r < 0.6) between the different antimicrobial-resistant genes belonging to certain antimicrobial classes. Besides, IncF plasmid showed a strong negative correlation ( r > −0.6) with IncHI2 and IncHI2A plasmids. Together, our study demonstrated antimicrobial-resistant S. enterica circulating in breeding chicken hatcheries in Henan province, highlighting the advanced approach, by using genomic characterization and statistical analysis, in conducting the routine monitoring of the emerging antimicrobial-resistant pathogens. Our findings also proposed that the day-old breeder chicks trading could be one of the potential pathways for the dissemination of multidrug-resistant S. enterica serovars.